Denken wie ein Philosoph, aber reden wie ein Bauer - Gruntar Jermol, Ada (Linguistica (Ljubljana), 2019)
Legislative acts are considered the most demanding types of legal texts. As norma-tive texts, they express rules of conduct by ordering, prohibiting or granting certain ac-tions or omissions. Although most of them have a clear macrostructure, their reception is made much more difficult by their "lack" of coherence. Like other normative texts, they are characterized by a high degree of abstraction, which results in a condensed and concise style that can be difficult to understand. Also, legislative acts differ from all other types of legal texts in that they are highly standardized in terms of language.They are generally characterized by an impersonal style with the use of indefinite pronouns and the passive voice as well as nominalizations. In general, normative legal texts are much more demanding than informative legal texts - even for experts, let alone for laypersons.In this article some basic characteristics of the German normative legal language are presented by taking into consideration the German Civil Code (BGB), which is regarded as a milestone of German law.
Keywords: abstraction; abstraktnost; German Civil Code (BGB); law; legal language; Nemški državljanski zakonik; normative text type; normativni besedilni tip; pravni jezik; zakon